2018
DOI: 10.1039/c8ob02734j
|View full text |Cite
|
Sign up to set email alerts
|

Practical regio- and stereoselective azidation and amination of terminal alkenes

Abstract: A metal-free synthesis of allylic azides and allylic amines was achieved under mild reaction conditions, which represents a milder alternative for azidation and amination reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…The following cinnamyl azides were prepared through known procedures and have been previously characterized: 1a , , 1c – 1d , , 1e – 1f , , 1g , , 1h , , 1j – 1k , , 1o , , 1p – 1q , 1t , ,, 1u – 1v , 1w , and 1hh . , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following cinnamyl azides were prepared through known procedures and have been previously characterized: 1a , , 1c – 1d , , 1e – 1f , , 1g , , 1h , , 1j – 1k , , 1o , , 1p – 1q , 1t , ,, 1u – 1v , 1w , and 1hh . , …”
Section: Methodsmentioning
confidence: 99%
“…Azide Synthesis. The following cinnamyl azides were prepared through known procedures and have been previously characterized: 1a, 44,45 1c−1d, 44,45 1e−1f, 44,46 1g, 44,47 1h, 18,44 1j−1k, 44,47 1o, 44,45 1p−1q, 44 1t, 46,48,49 1u−1v, 30 1w, 49−51 and 1hh. 18,44 2-Nitrocinnamylazide (1b).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…For example­, in a typical experiment using an H-Cube ® , ( S )- 7 gave the saturated N -Boc-protected sulfone ( S )- 8 in reasonably good yield (Scheme 2 ). Alternative methods reported for the conversion of azides into amides and carbamates, including, for example, traceless Staudinger reactions 11 and hydrogenolysis with Lindlar’s catalyst, 12 proved not to be feasible for the synthesis of 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The yields for the KO t Bu-mediated transformation are presented below in Tables –, whereas the yields using DBU are shown in the Supporting Information (Tables SI, 1–3). This study was performed to compare the result from our recently reported regio-and stereoselective nucleophilic addition to miscellaneous terminal olefins. , In our prior work, DBU was the best base to afford allylic adducts from electron-poor or weak electron-donating substrates. However, for this work, KO t Bu was deemed superior base for the observed rearrangement of electron-rich substrates (i.e., estragole and safrole).…”
Section: Resultsmentioning
confidence: 99%